Pengembangan Agrowisata di Nagari Lasi Kecamatan Canduang Kabupaten Agam Berbasis Masyarakat - Rosita Melia Nopisi; Metria Dicky Putra (Universitas Muhammadiyah Palembang, 2024)
This activity offers an experience of the agricultural production process and promotes local wisdom and agricultural products to visitors. This article uses a qualitative descriptive research method with primary data collection through in-depth interviews, field observations, and documentation. The research results show that the people of Nagari Lasi support the development of tourism in their area, with the majority agreeing or supporting the construction of tourist attractions in Nagari Lasi. The article discusses the agrotourism environment in Nagari Lasi, the condition of tourist attractions, the efforts of the local community in managing agrotourism, and the involvement of the government in tourism development. The management of agrotourism in Nagari Lasi involves both the community and the government as an effort to achieve the welfare of the community in the future. From this research, it can be concluded that the development of agrotourism in Nagari Lasi has great potential to improve the economy, environmental preservation, and the welfare of the local community. The contribution of agritourism to the development of tourism in Nagari Lasi shows that integrated management can provide significant benefits to the region.